The Impact of Exploitation and Exploration on Export Sales Growth: The Moderating Role of Domestic and International Collaborations. Issue 4 (December 2020) - Sousa, Carlos M.P.; Li, Rebecca Yu; He, Xinming
This study examines the short- and long-term implications of the impact of exploitation and exploration on export sales growth. It also explores the moderating role of external collaborations by differentiating between domestic collaborations and international collaborations. The authors tested their conceptual model with data from the U.K. Community Innovation Survey (2010–2016). Using different time lags for exploitation and exploration, the findings indicate that the impact varies over time. Specifically, they reveal that the effect of exploitation is negative in the long term but positive in the short term, while exploration has no significant effect in the short term but a positive influence on export sales growth in the long term. Similarly, the moderating effect of domestic and international collaborations has been found to vary over time. The authors conclude with a discussion of the theoretical and practical implications.